Electrochemical device and electronic device
By using a 0.5μm~18μm porous layer and 25%~55% propyl propionate in the electrolyte in the isolation film of the lithium-ion battery, the problem of long charging time and fast charging affecting the cycle performance and safety performance of the lithium-ion battery is solved. problem, achieving excellent fast charging performance, low gas production and high safety of the battery.
Patent Information
- Application Number
- CN202411907519.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-01-24
AI Technical Summary
Lithium-ion batteries are charged for a long time during charging, and are likely to affect the battery's cycle performance and safety performance during fast charging.
The porous layer of the isolation membrane is 0.5 μm ~ 18 μm, and propionate is added to the electrolyte. The mass content of propionate is 25%to 55%.
Improving the fast charge performance of electrochemical devices, reducing the gas production when charging, thereby improving the cycle performance and safety performance of the battery.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical energy storage, and in particular to an electrochemical device and an electronic device. Background Art
[0002] With the diversified demand for the application scenarios of electrochemical devices such as lithium-ion batteries, lithium-ion batteries, which are widely used in portable electronic devices, drones, electric cleaning tools, electronic cars, electric vehicles, and household energy storage equipment, are constantly pursuing higher operating voltages, higher energy densities, and excellent performance of batteries at high and low temperatures. With the widespread application of lithium-ion batteries, a huge demand from users is that the charging time needs to be shortened as much as possible, but reducing the charging time of lithium-ion batteries can easily have a significant adverse effect on the cycle performance and safety performance of lithium-ion batteries. Summary of the invention
[0003] The present application provides an electrochemical device and an electronic device. The electrochemical device of the present application has good fast charging performance; and the electrochemical device of the present application has a low gas production when overcharged, so the electrochemical device of the present application also has good cycle performance and safety performance.
[0004] In a first aspect, the present application provides an electrochemical device comprising an isolation membrane, a positive electrode plate and an electrolyte, wherein the isolation membrane comprises a porous layer, and the average pore size of the porous layer is 0.5 μm to 18 μm; the electrolyte contains propyl propionate, and the mass content of propyl propionate is 25% to 55% based on the mass of the electrolyte.
[0005] Based on the electrochemical device of the present application, the average pore size in the porous layer of the isolation membrane is 0.5μm to 18μm, which has a good ion transmission effect and can reduce the fast charging time of the electrochemical device. In addition, the conventional porous layer has a certain structural instability and poor mechanical strength due to the porous structure caused by the chemical microstructure. In the electrochemical device of the present application, the electrolyte contains propyl propionate, and the mass content of propyl propionate is in the range of 25% to 55%, which can enhance the structural stability and mechanical strength of the porous layer, so that when overcharged under high temperature conditions, the gas production in the electrochemical device can be reduced, so that the electrochemical device has better cycle performance and safety performance.
[0006] In a possible implementation, the average pore size of the porous layer is 0.5 μm to 10 μm.
[0007] In the above technical solution, the average pore size of the porous layer is in the range of 0.5 μm to 10 μm, which is beneficial to further improve the fast charging performance of the electrochemical device and reduce the gas production of the electrochemical device.
[0008] In a possible implementation, the average pore size of the porous layer is 5 μm to 10 μm.
[0009] In the above technical solution, the average pore size of the porous layer is 5 μm to 10 μm, which is beneficial to further improve the fast charging performance of the electrochemical device and reduce the gas production of the electrochemical device.
[0010] In a possible implementation, based on the mass of the electrolyte, the mass content of propyl propionate is 30.5%~45%.
[0011] In the above technical solution, the fast charging performance of the electrochemical device can be further improved and the gas production can be further reduced.
[0012] In a possible implementation, based on the mass of the electrolyte, the mass content of propyl propionate is 30.5% to 38.5%.
[0013] In the above technical solution, the fast charging performance of the electrochemical device can be further improved and the gas production can be further reduced.
[0014] In a possible implementation, the electrochemical device satisfies at least one of the following conditions (1) to (4): (1) the thickness of the porous layer is 0.5 μm to 5 μm; (2) the porous layer contains 45 to 95 pore structures; (3) the porous layer includes inorganic particles and a polymer of vinylidene fluoride and hexafluoropropylene; (4) the porous layer includes inorganic particles, and the aspect ratio of the inorganic particles is 1:5 to 1:1.
[0015] In a possible implementation, the positive electrode plate has a protrusion, and the height H1 of the protrusion satisfies: 20 μm≤H1≤70 μm.
[0016] In the above technical solution, the bumps on the positive electrode plate can play a role in suppressing the volume expansion of the electrochemical device under high-temperature storage. Moreover, due to the presence of the bumps, there is a gap between the isolation membrane and the positive electrode plate that can accommodate the electrolyte, and the isolation membrane can be fully wetted by the electrolyte, which enables the electrochemical device to still have a good capacity retention rate after fast charging.
[0017] In a possible implementation, the positive electrode plate includes a positive electrode active material layer, the positive electrode active material layer includes a conductive agent, the conductive agent includes at least one of conductive carbon black and Ketjen black, and the specific surface area of the conductive agent is 600m 2 / g~1100m 2 / g.
[0018] In the above technical solution, conductive carbon black and Ketjen black with a specific specific surface area can improve the capacity retention rate of the electrochemical device after fast charging and inhibit the volume expansion of the electrochemical device under high-temperature storage.
[0019] In one possible implementation, the coating surface density of the positive electrode sheet is 220 mg / 1540.25 mm 2 ~320mg / 1540.25mm 2 .
[0020] In the above technical solution, the capacity retention rate of the electrochemical device after fast charging can be further improved, and the volume expansion at high temperature can be better suppressed.
[0021] In one possible implementation, the positive electrode plate includes a binder, the binder includes a first substance, the functional group of the first substance includes a trihydroxybenzene ring, and based on X-ray diffraction characterization, the first substance has n peaks within the diffraction angle range of 50°~70°, satisfying: 1≤n≤4.
[0022] In the above technical solution, the first substance in the binder can improve the capacity retention rate of the electrochemical device after fast charging, can capture the gas molecules generated by the side reactions at the interface between the electrolyte and the electrode, and inhibit the volume expansion of the electrochemical device at high temperature.
[0023] In a possible implementation, the positive electrode active material layer includes aluminum element. Based on the mass of the positive electrode active material layer, the mass content of the aluminum element is T ppm. The thickness of the positive electrode plate is C μm, satisfying: 41.6≤T / C≤77.8.
[0024] In the above technical solution, the safety performance of the electrochemical device after overcharging can be further improved, and the capacity retention rate at low temperatures is also high.
[0025] In one possible implementation, 5000≤T≤6400.
[0026] In the above technical solution, the safety performance of the electrochemical device after overcharging and the capacity retention rate at low temperature can be further improved.
[0027] In a possible implementation, the electrolyte includes lithium difluorophosphate and diethyl carbonate. Based on the total mass of the electrolyte, the mass content of lithium difluorophosphate is X%, the mass content of diethyl carbonate is Y%, and the following conditions are satisfied: 11.1≤Y / X≤500.
[0028] In the above scheme, the safety performance of the electrochemical device after overcharging can be further improved, and the capacity retention rate at low temperatures is also high.
[0029] In one possible implementation, 20≤Y / X≤360.
[0030] In the above technical solution, the safety performance of the electrochemical device after overcharging and the capacity retention rate at low temperature can be further improved.
[0031] In a possible implementation, the electrolyte includes lithium bis(fluorosulfonyl)imide, and the mass content of the lithium bis(fluorosulfonyl)imide is Z% based on the total mass of the electrolyte, satisfying: 0.4≤Z≤1.8.
[0032] In the above scheme, the safety performance of the electrochemical device after overcharging can be further improved, and the capacity retention rate at low temperatures is also high.
[0033] In a second aspect, the present application provides an electronic device, which includes the above-mentioned electrochemical device. Therefore, the electronic device of the present application has good performance.
[0034] Beneficial effects of this application: The present application provides an electrochemical device and an electronic device, wherein the electrochemical device includes a separator, a positive electrode plate and an electrolyte, wherein the average pore size of the porous layer of the separator is 0.5 μm to 18 μm; the electrolyte includes propyl propionate, and based on the mass of the electrolyte, the mass content of propyl propionate is 25% to 55%. Through the synergistic effect of the separator and the electrolyte, the electrochemical device of the present application not only has good fast charging performance, but also has low gas production, so that the electrochemical device has good cycle performance and safety performance. DETAILED DESCRIPTION
[0035] The embodiments of the present application will be described in detail below. The embodiments of the present application should not be interpreted as limiting the present application.
[0036] As used in this application, the terms "including," "containing," and "comprising" are used in their open, non-limiting sense.
[0037] In addition, sometimes amounts, ratios and other numerical values are presented in range format herein. It should be understood that such range format is for convenience and brevity, and should be flexibly understood to include not only the numerical values explicitly specified as range limits, but also all individual numerical values or sub-ranges encompassed within the range, as if each numerical value and sub-range were explicitly specified.
[0038] In the detailed description and claims, a list of items connected by the terms "one or more of," "one or more of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A or B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, or C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0039] The electrochemical device and the electronic device of the present application are described in detail below.
[0040] In the first aspect, the present application provides an electrochemical device, which includes a separator, a pole piece, and an electrolyte. In the electrochemical device of the present application, the porous layer in the separator can make the electrochemical device have good ion transmission performance, and the propyl propionate in the electrolyte can improve the structural stability and mechanical strength of the separator. Therefore, the electrochemical device of the present application has good ion transmission performance, low gas production when overcharged under high temperature conditions, and good cycle performance and safety performance.
[0041] The structure of the electrochemical device of the present application is as follows: Isolation film The separator of the present application includes a porous layer, and the average pore size of the porous layer is 0.5μm~18μm, so that the electrochemical device can have a good ion transmission effect, thereby reducing the fast charging time of the electrochemical device and improving the fast charging performance of the electrochemical device; if the average pore size is too small, it will hinder the ion transmission, and if it is too large, the effect of improving the ion transmission is not obvious, but it is easy to increase the risk of short circuit and reduce the safety performance of the electrochemical device. For example, the average pore size of the porous layer can be 0.5μm, 1μm, 3μm, 5μm, 8μm, 10μm, 14μm, 16μm, 18μm, etc. or within the range composed of any two of the above values. Preferably, the average pore size of the porous layer can be 0.5μm~10μm, and further preferably, the average pore size of the porous layer can be 0.5μm~5μm.
[0042] In some embodiments of the present application, the thickness of the porous layer is generally 0.5 μm to 5 μm, and the porous layer may contain 45 to 90 pore structures, so that the isolation membrane can have both good mechanical strength and excellent ion transmission effect.
[0043] In addition, in some embodiments of the present application, the porous layer includes inorganic particles and a polymer of vinylidene fluoride and hexafluoropropylene. The aspect ratio of the inorganic particles is generally in the range of 1:5 to 1:1. This can further improve the fast charging performance of the electrochemical device and reduce the gas production of the electrochemical device, thereby further improving the cycle performance and safety performance of the electrochemical device.
[0044] Electrolyte In the electrochemical device of the present application, the electrolyte includes propyl propionate, and based on the total mass of the electrolyte, the mass content of propyl propionate is 25%~55%, specifically 25%, 28%, 30.5%, 35%, 38.5%, 40%, 45%, 55%, etc. or within the range composed of any two of the above values.
[0045] The inventors found that the porous structure of the porous layer easily leads to structural instability and poor mechanical strength of the separator; and the inventors also found that when the electrolyte includes the above-mentioned content of propyl propionate, the structural stability and mechanical strength of the porous layer can be enhanced, so that when overcharged under high temperature conditions, the gas production in the electrochemical device can be reduced, with better cycle performance and safety performance. Preferably, based on the total mass of the electrolyte, the mass content of propyl propionate is 30.5% to 45%, and more preferably, the mass content of propyl propionate is 30.5% to 38.5%.
[0046] In some embodiments of the present application, the electrolyte also includes lithium difluorophosphate and diethyl phosphate, and based on the mass of the electrolyte, the mass content of lithium difluorophosphate is X%, and the mass content of diethyl phosphate is Y%, 11.1≤Y / X≤500, preferably 20≤Y / X≤360; the inventors found that when the electrolyte contains lithium difluorophosphate and diethyl phosphate within the above range, the safety performance of the electrochemical device after overcharging can be further improved, and the capacity retention rate of the electrochemical device at low temperature can also be significantly improved. Specifically, in some embodiments of the present application, X can be 0.05, 0.1, 0.15, 0.2, 0.3, 0.5, 0.6, 0.9, etc. or within the range consisting of any two of the above values, and Y can be 10, 13, 18, 20, 23, 25, etc. or within the range consisting of any two of the above values; wherein X is preferably 0.05~0.5, and Y is preferably 10~18.
[0047] In addition, in order to improve the safety performance of the electrochemical device after overcharging and the electrical performance of the electrochemical device at low temperatures, in some embodiments of the present application, the electrolyte also includes lithium bis(fluorosulfonyl)imide. Based on the total mass of the electrolyte, the mass content of lithium bis(fluorosulfonyl)imide is Z%, satisfying: 0.4≤Z≤1.8.
[0048] Positive electrode In the present application, the structure of the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer contains components such as positive electrode active material, conductive agent and binder. The "positive electrode active material layer disposed on at least one surface of the positive electrode current collector" means that the positive electrode active material layer can be disposed on one surface in the thickness direction of the positive electrode current collector, or on two surfaces in the thickness direction of the positive electrode current collector. Moreover, in the present application, the "surface of the positive electrode current collector" can be the entire area of the positive electrode current collector, or it can be a partial area of the positive electrode current collector. There is no special limitation in the present application, as long as the purpose of the present application can be achieved.
[0049] In some embodiments of the present application, the surface of the positive electrode plate has convex points (i.e., the surface of the positive electrode active material layer has convex points), and the height H1 of the convex points relative to the surface of the positive electrode plate satisfies: 20μm≤H1≤70μm. The convex points on the positive electrode plate can play a role in suppressing the volume expansion of the electrochemical device at high temperature, and due to the presence of the convex points, there is a gap between the separator and the positive electrode plate that can accommodate the electrolyte, and the separator can be fully wetted by the electrolyte, which enables the electrochemical device to still have a good capacity retention rate after fast charging.
[0050] In some embodiments of the present application, in the positive electrode active material layer, the conductive agent includes at least one of conductive carbon black or Ketjen black, and the specific surface area (BET) of the conductive agent is generally 600 m 2 / g~1100m 2 / g. This can improve the capacity retention rate of the electrochemical device after fast charging and inhibit the volume expansion of the electrochemical device at high temperature.
[0051] Of course, in some other embodiments of the present application, the conductive agent may also be carbon nanotubes or graphene.
[0052] In some embodiments of the present application, in the positive active material layer of the positive electrode sheet, the binder includes a first substance, the first substance has a trihydroxybenzene ring functional group, and based on X-ray diffraction (XRD) characterization, the first substance has n peaks in the diffraction angle range of 50°~70°, satisfying: 1≤n≤4. This can also improve the capacity retention rate of the electrochemical device after fast charging and inhibit the volume expansion of the electrochemical device at high temperature. For example, the first substance can be a polymer, and its structural units include but are not limited to . The present application does not specifically limit the specific structure and type of the first substance, as long as it contains a trihydroxybenzene ring and can meet the purpose of the present application. Of course, in some other embodiments of the present application, the binder in the positive electrode plate may also include but is not limited to any one or at least two of the following: polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, nitrocellulose and other resin-based polymers; styrene-butadiene rubber (SBR), nitrile rubber (NBR), fluororubber, isoprene rubber, polybutadiene rubber, ethylene-propylene rubber and other rubber-like polymers; styrene-butadiene-styrene block copolymers or their hydrides, ethylene-propylene-diene terpolymers Thermoplastic elastomeric polymers such as EPDM, styrene-ethylene-butadiene-ethylene copolymers, styrene-isoprene-styrene block copolymers or their hydrogenated products; soft resinous polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymers, propylene-α-olefin copolymers; fluorine-based polymers such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene, fluorinated polyvinylidene fluoride, polytetrafluoroethylene-ethylene copolymers; polymer compositions having ion conductivity of alkali metal ions (especially lithium ions), etc.
[0053] In addition, in some embodiments of the present application, the positive electrode active material layer includes aluminum element, and based on the mass of the positive electrode active material layer, the mass content of the aluminum element is T ppm, and the value of T and the thickness Cμm of the positive electrode plate can satisfy: 41.6≤T / C≤77.8. As an example, the values of C and T can be: C∈[90,120]μm, T∈[5000,7000]ppm, preferably T∈[5000,6400]ppm, which can improve the safety performance of the electrochemical device after overcharging and the capacity retention rate at low temperature.
[0054] The aluminum element can come from the positive electrode active material or from the inorganic particles of the isolation membrane. This application does not specifically limit the positive electrode active material, as long as it can meet the purpose of this application. For example, the positive electrode active material includes but is not limited to at least one of lithium iron phosphate (LiFePO4), lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium nickel oxide, ternary materials, etc., and ternary materials include but are not limited to LiNi x Co y Mn z O2、LiNi x Co y Al z O2, etc., and the content of Ni, Co, Mn, Al, etc. can be adjusted to ensure that x+y+z=1. For example, the ternary material can be LiNi 0.6 Co 0.2 Mn 0.2O2、LiNi 0.88 Co 0.08 Mn 0.04 O2、LiNi 0.8 Co 0.15 Mn 0.05 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.88 Co 0.1 Mn 0.02 O2、LiNi 0.8 Co 0.15 Al 0.05 O2、LiNi 0.88 Co 0.1 Al 0.02 O2, etc.
[0055] In some embodiments of the present application, the coating surface density of the positive electrode sheet is generally 220 mg / 1540.25 mm 2 ~320mg / 1540.25mm 2 This is also beneficial to improving the safety performance of the electrochemical device after overcharging and the capacity retention rate at low temperatures.
[0056] In the positive electrode sheet, the type of positive current collector is not particularly limited, and it can be any material known to be suitable for use as a positive current collector. The material of the positive current collector includes, but is not limited to, metal materials such as aluminum, stainless steel, nickel plating, titanium, and tantalum. In addition, in order to reduce the electronic contact resistance between the positive current collector and the positive active material layer, a conductive additive or a conductive coating may be provided on the surface of the positive current collector. The conductive additive includes, but is not limited to, carbon and precious metals such as gold, platinum, and silver. The conductive coating may be a mixture layer of an inorganic oxide, a conductive agent, and a positive electrode binder.
[0057] When preparing the positive electrode sheet, the components in the above-mentioned positive electrode active material layer can be dissolved or dispersed in a liquid solvent to prepare a positive electrode slurry, and then the positive electrode slurry is coated on the positive electrode collector and dried to form a positive electrode active material layer on the positive electrode collector, thereby obtaining a positive electrode sheet. When using this method to prepare the positive electrode sheet, there is no special restriction on the solvent in the positive electrode slurry, as long as it can dissolve or disperse the above-mentioned components. Specifically, the solvent in the positive electrode slurry includes but is not limited to N-methylpyrrolidone (NMP), ethylene carbonate (EC), etc. In addition, when preparing the positive electrode sheet, the various components in the positive electrode active material layer can also be dry mixed to form a sheet, and then the obtained sheet can be pressed onto the positive electrode collector.
[0058] Negative electrode The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, and the components of the negative electrode active material layer include negative electrode active materials. That is, in the present application, the negative electrode active material layer can be disposed on one surface in the thickness direction of the negative electrode current collector, or on two surfaces in the thickness direction of the negative electrode current collector. Moreover, in the present application, the "surface of the negative electrode current collector" can be the entire area of the negative electrode current collector, or it can be a partial area of the negative electrode current collector. There is no special limitation in the present application, as long as the purpose of the present application can be achieved.
[0059] The negative electrode active material layer generally contains negative electrode active materials, and the present application does not have any particular restrictions on the negative electrode active materials. Specifically, the negative electrode active material may include at least one of a carbon material or a silicon-based material. More specifically, the carbon material includes but is not limited to at least one of natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon or soft carbon; the silicon-based material includes but is not limited to at least one of silicon, silicon-oxygen composite materials or silicon-carbon composite materials.
[0060] In some embodiments, the negative electrode active material layer generally further contains a negative electrode conductive agent. The present application has no particular restrictions on the type of the negative electrode conductive agent, as long as the purpose of the present application can be achieved. For example, the negative electrode conductive agent includes but is not limited to at least one of acetylene black, Ketjen black, carbon nanotubes, carbon fibers, carbon dots or graphene.
[0061] In some embodiments, the negative electrode active material layer may also contain a negative electrode binder and a thickener. The present application has no particular restrictions on the types of the negative electrode binder and the thickener, as long as the purpose of the present application can be achieved. For example, the negative electrode binder may include but is not limited to at least one of polyvinyl alcohol, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber or acrylic (ester) styrene-butadiene rubber; the thickener in the negative electrode slurry may include but is not limited to at least one of sodium carboxymethyl cellulose or lithium carboxymethyl cellulose.
[0062] In the negative electrode sheet, the material of the negative electrode current collector includes but is not limited to copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a polymer substrate covered with a conductive metal, etc., and there is no special limitation in this application. Among them, the conductive metal includes but is not limited to copper, nickel or titanium, and the material of the polymer substrate includes but is not limited to at least one of polyethylene, polypropylene, ethylene propylene copolymer, polyethylene terephthalate, polyethylene naphthalate or poly(p-phenylene terephthalamide).
[0063] In addition, in the present application, there is no particular limitation on the thickness of the negative electrode current collector and the negative electrode active material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4 μm to 12 μm, and the thickness of the single-sided negative electrode active material layer is 30 μm to 160 μm.
[0064] In addition, similar to the preparation of the positive electrode sheet, when preparing the negative electrode sheet, it can be configured into a negative electrode slurry, and then the negative electrode slurry is coated on the negative electrode collector and dried to form a negative electrode active material layer on the negative electrode collector to obtain a negative electrode sheet; or the components in the negative electrode active material layer can be dry mixed to form a sheet, and then the obtained sheet is pressed onto the negative electrode collector to form a negative electrode active material layer, thereby obtaining a negative electrode sheet. The solvent in the negative electrode slurry includes any one of an aqueous solvent and an organic solvent. The aqueous solvent includes but is not limited to a mixed solvent of alcohol and water or water. Organic solvents include, but are not limited to, aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, and methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N,N-dimethylaminopropylamine; ethers such as diethyl ether, propylene oxide, and tetrahydrofuran (THF); amides such as N-methylpyrrolidone (NMP), dimethylformamide, and dimethylacetamide; aprotic polar solvents such as hexamethylphosphoramide and dimethyl sulfoxide. In addition, in some other embodiments, when using an aqueous solvent, the components of the negative electrode slurry will also include a thickener and styrene-butadiene rubber (SBR) emulsion to slurry the negative electrode slurry, thereby adjusting the viscosity of the negative electrode slurry. The types of thickeners in the positive electrode slurry include, but are not limited to, at least one of carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and their salts.
[0065] The electrochemical device of the present application also includes a packaging bag for containing a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, as well as other components known in the art in the electrochemical device, and the present application does not limit the above other components. The present application does not specifically limit the packaging bag, and it can be a packaging bag known in the art, as long as it can achieve the purpose of the present application.
[0066] In a second aspect, the present application further provides an electronic device, which includes the electrochemical device according to the present application.
[0067] The use of the electrochemical device of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. In some embodiments, the electrochemical device of the present application can be used for, but not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.
[0068] Example The following uses lithium-ion secondary batteries as an example to provide examples and comparative examples to more specifically describe the implementation of the electrochemical device of the present application. Those skilled in the art will understand that the preparation method described in the present application is only an example, and any other suitable preparation method is within the scope of the present application.
[0069] Test methods and equipment Fast charge test retention rate determination: At -10°C, the lithium ion batteries prepared in the embodiments and comparative examples were subjected to constant current charging tests at a rate of 1.5C, and the rate charging capacity retention rate was calculated, where the rate charging retention rate of the battery at 1.5C = the capacity of the battery after charging at a rate of 1.5C / the capacity of the battery after charging at a rate of 0.5C).
[0070] -10℃ interval cycle test: Before the test, the thickness D0 of the fully charged battery cell was tested, and the battery was placed in a (-10±3)℃ environment and allowed to stand for 3 hours. When the battery cell reached (-10±3)℃, the battery was charged to 4.5V at a constant current of 0.8C, and charged to a cut-off current of 0.05C at a constant voltage of 4.5V, and allowed to stand at -10℃ for 6 hours, ensuring that the constant current and constant voltage charging time plus the standing time was 24h, and then discharged at 0.5C, and the initial energy E0 was recorded. This cycle was repeated. When the cycle reached the required number of times, the discharge energy was used as the battery's energy E1, and the energy retention rate (%) was calculated, where energy retention rate (%) = E1 / E0×100%.
[0071] Gas production test: At 25°C, the battery was cycled 20 times at a rate of 1C with a test voltage of 2.0V~4.5V. A battery gas production test device was used to detect the gas production after the battery cycle.
[0072] Overcharge test pass rate: At (45±5)℃, the discharged battery cell is charged at 3.5C constant current to 5.0V, then changed to constant voltage charging, and the charging time is limited to 6 hours or the charging is stopped when the battery surface temperature is stable (temperature difference within 30min≤2℃). Judgment standard: the battery cell does not catch fire, and each embodiment is tested with 20 parallel samples as a group.
[0073] High temperature (75°C) storage volume expansion test: At room temperature, the battery was charged at a constant current of 2C to the charge cut-off voltage, and then charged at a constant voltage until the current dropped to 0.1C, and then stored in a constant temperature oven at 75°C for 15 hours. The volume change rate before and after high-temperature storage was recorded.
[0074] 5C full charge time test: Take the finished battery cell, discharge it at 0.7C to the set value (the voltage of LCO for the positive electrode active material is 3.0V) at 25°C; then charge it at 5C to the cut-off voltage, and then charge it to 0.05C with the cut-off voltage, and record the time of the whole charging process.
[0075] Test of high temperature cycle capacity retention rate of lithium-ion batteries: At 45°C, the lithium-ion battery is charged to 4.5V at 1C constant current, then charged to 0.05C at 4.5V constant voltage, and then discharged to 3.0V at 0.8C constant current. This is the first cycle. The lithium-ion battery is cycled 300 times under the above conditions. "1C" refers to the current value that completely discharges the battery capacity within 1 hour.
[0076] The cycle capacity retention rate of the lithium ion battery was calculated by the following formula: Capacity retention rate after 300 cycles = (discharge capacity at the 300th cycle / discharge capacity at the first cycle) × 100%.
[0077] Electrolyte component analysis test: The GC-MS (gas chromatography-mass spectrometry) and IC (ion chromatography) testing methods were used in combination with the external standard method for analysis and testing.
[0078] Example 1-1 <Preparation of Electrolyte> In an argon atmosphere glove box with a water content of less than 10 ppm, ethyl methyl carbonate and ethyl acetate were mixed in a mass percentage of 1:1 to prepare a basic solvent, and then lithium salt lithium hexafluorophosphate (LiPF6), propyl propionate, lithium difluorophosphate, diethyl carbonate and lithium bis(fluorosulfonyl)imide were added to form an electrolyte. Based on the total mass of the electrolyte, the mass percentage of LiPF6 was 9%, the mass contents of propyl propionate, lithium difluorophosphate, diethyl carbonate and lithium bis(fluorosulfonyl)imide are shown in Tables 1 and 3, and the remainder is the basic solvent.
[0079] <Preparation of Separator Film> A 6 μm thick polyethylene (PE) microporous membrane was selected as the substrate of the isolation membrane, and then inorganic particles boehmite with an aspect ratio of 1:1 and polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) were dispersed in deionized water at a mass ratio of 85:15 to form a porous layer slurry with a solid content of 48%; the porous layer slurry was coated on both surfaces of the PE substrate by gravure roller coating and then dried to form a porous layer adhered to the surface of the PE substrate, the thickness of the porous layer was 2 μm, the average pore size was 0.5 μm, and the number of pore structures in each porous layer was 50; the parameters of the porous layer of the isolation membrane are shown in Table 2.
[0080] <Preparation of positive electrode sheet> The positive electrode active material lithium cobalt oxide, the conductive agent conductive carbon black, and the first binder material are mixed in a mass ratio of 95:2:3, and N-methylpyrrolidone (NMP) is added. The mixture is stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 70wt%. The positive electrode slurry is evenly coated on the upper and lower surfaces of the positive electrode current collector aluminum foil, dried, and pressurized, and then cut into a specified size to obtain a positive electrode sheet. Then, a convex point is rolled out on the surface of the positive electrode sheet by rolling, and the height H1 of the convex point is 20μm.
[0081] The BET of conductive carbon black is 700m 2 / g, and XRD characterization shows that there are 4 peaks at diffraction angles of 50°~70°. The coating surface density of the prepared positive electrode sheet is 220mg / 1540.25mm 2 , the thickness C is 100 μm, and based on the mass of the positive electrode active material layer, the content of aluminum element is 5000 ppm; the specific parameters of the positive electrode sheet are shown in Tables 2 and 3.
[0082] <Preparation of negative electrode sheet> Artificial graphite, styrene-butadiene rubber (SBR), polyacrylic acid (PAA), carbon nanotubes (CNT), and carboxymethyl cellulose (CMC) were mixed in a mass ratio of 95.8:2.4:0.5:0.5:0.8, and then deionized water was added as a solvent and stirred evenly to prepare a negative electrode slurry with a solid content of 45wt%. The negative electrode slurry was evenly coated on the upper and lower surfaces of the negative electrode current collector copper foil, dried, pressurized, and then cut into a specified size to obtain a negative electrode sheet.
[0083] <Preparation of electrochemical device> The prepared positive electrode, separator, negative electrode and separator are stacked in order, so that the separator is between the positive electrode and the negative electrode to play a role of isolation, and then wound to obtain an electrode assembly. After welding the pole ear, the electrode assembly is placed in an aluminum plastic film packaging bag, placed in a vacuum oven at 85°C for 12 hours to remove moisture, and the prepared electrolyte is injected. After vacuum packaging, standing, formation, shaping, and capacity testing, a lithium-ion battery is obtained.
[0084] Example 1-2 to Example 1-32 Except for adjusting the corresponding parameters according to Table 1, the rest is basically the same as Example 1-1.
[0085] Comparative Examples 1 to 6 Except for adjusting the corresponding parameters according to Table 1, the rest is basically the same as Example 1-1.
[0086] Table 1
[0087] Example 2-1 to Example 2-27 Except for adjusting the parameters in the positive electrode sheet according to Table 2, the rest is basically the same as Example 1-1. In addition, in Example 2-27, the binder in the positive electrode sheet is PVDF.
[0088] Table 2
[0089] Note: The “number of characteristic peaks” in Table 2 refers to the number of characteristic peaks of the first substance within the diffraction angle range of 50°~70° during XRD characterization; H1 represents the height of the convex point.
[0090] Example 3-1 to Example 3-40 Except for adjusting the parameters in the positive electrode plate and the electrolyte according to Table 3, the rest is basically the same as Example 1-1.
[0091] Table 3
[0092] Note: In Table 3, X%, Y% and Z% represent the mass contents of lithium difluorophosphate, diethyl dicarbonate and lithium bis(fluorosulfonyl)imide based on the total mass of the electrolyte; T ppm represents the mass content of aluminum element based on the mass of the positive electrode active material layer. C μm represents the thickness of the positive electrode sheet.
[0093] It can be seen from Table 1 that in the electrochemical device of the present application, when the average pore size of the porous layer is 0.5 μm~18 μm and the content of propyl propionate in the electrolyte is 25%~55%, the fast charging time of the electrochemical device is short and the gas production is small, so the electrochemical device has excellent fast charging performance, cycle performance and safety performance.
[0094] In particular, it can be seen from Table 2 that by controlling the bump height of the positive electrode plate, the type of conductive agent, the BET of the conductive agent, the coating surface density of the positive electrode plate, and the type of binder in the present application, the capacity retention rate of the electrochemical device under fast charging can be improved and the volume expansion rate during high-temperature storage can be suppressed.
[0095] In particular, as shown in Table 3, by controlling lithium difluorophosphate, diethyl carbonate and lithium bis(fluorosulfonyl)imide in the electrolyte, as well as the thickness of the positive electrode sheet and the content of aluminum in the positive electrode sheet, the energy retention rate of the electrochemical device at low temperature and the safety performance under overcharge can be improved.
[0096] The above are only embodiments of the present application and are not intended to limit the scope of protection of the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the scope of protection of the present application.
Claims
1. An electrochemical device, characterized in that: It includes a separator, a positive electrode sheet and an electrolyte, wherein the separator includes a porous layer, and the average pore size of the porous layer is 0.5 μm to 18 μm; The electrolyte includes propyl propionate, and the mass content of the propyl propionate is 25% to 55% based on the mass of the electrolyte; The positive electrode sheet includes a positive electrode active material layer, the positive electrode active material layer includes a conductive agent, the conductive agent includes at least one of conductive carbon black and Ketjen black, and the specific surface area of the conductive agent is 600m 2 / g~1100m 2 / g.
2. The electrochemical device according to claim 1, characterized in that The average pore size of the porous layer is 0.5 μm to 10 μm.
3. The electrochemical device according to claim 2, characterized in that The average pore size of the porous layer is 5 μm to 10 μm.
4. The electrochemical device according to claim 1, characterized in that Based on the mass of the electrolyte, the mass content of the propyl propionate is 30.5% to 45%.
5. The electrochemical device according to claim 4, characterized in that Based on the mass of the electrolyte, the mass content of the propyl propionate is 30.5% to 38.5%.
6. The electrochemical device according to claim 1, characterized in that It satisfies at least one of the following conditions (1) to (4): (1) The thickness of the porous layer is 0.5 μm to 5 μm; (2) The porous layer contains 45 to 95 pore structures; (3) The porous layer includes inorganic particles and a polymer of vinylidene fluoride and hexafluoropropylene; (4) The porous layer includes inorganic particles, and the aspect ratio of the inorganic particles is 1:5 to 1:
1.
7. The electrochemical device according to claim 1, characterized in that The positive electrode plate has a convex point, and the convex point height H1 satisfies: 20μm≤H1≤70μm.
8. The electrochemical device according to claim 1, characterized in that The coating surface density of the positive electrode sheet is 220mg / 1540.25mm 2 ~320mg / 1540.25mm 2 .
9. The electrochemical device according to claim 1, characterized in that The positive electrode plate includes a binder, the binder includes a first substance, the functional group of the first substance includes a trihydroxybenzene ring, and based on X-ray diffraction characterization, the first substance has n peaks within the diffraction angle range of 50°~70°, satisfying: 1≤n≤4.
10. The electrochemical device according to claim 1, characterized in that The positive electrode active material layer includes aluminum element. Based on the mass of the positive electrode active material layer, the mass content of the aluminum element is T ppm. The thickness of the positive electrode plate is C μm, satisfying: 41.6≤T / C≤77.
8.
11. The electrochemical device according to claim 10, characterized in that 5000≤T≤6400。 12. The electrochemical device according to claim 1, characterized in that The electrolyte includes lithium difluorophosphate and diethyl carbonate. Based on the total mass of the electrolyte, the mass content of the lithium difluorophosphate is X%, and the mass content of the diethyl carbonate is Y%, satisfying: 11.1≤Y / X≤500.
13. The electrochemical device according to claim 12, characterized in that 20≤Y / X≤360.
14. The electrochemical device according to claim 1, characterized in that The electrolyte includes lithium bis(fluorosulfonyl)imide. Based on the total mass of the electrolyte, the mass content of the lithium bis(fluorosulfonyl)imide is Z%, satisfying: 0.4≤Z≤1.
8.
15. An electronic device comprising the electrochemical device according to any one of claims 1 to 14.
Citation Information
Patent Citations
Electrolyte and lithium ion battery
CN109935906A
Electrochemical device and electronic device
CN115606030A
Electrochemical device and electronic device
CN116404265A
Electrolyte, electrochemical device and electronic device
CN119170869A
Curable coating composition
JP1988248869A
Cited By
Battery and electric device
CN120165038A